2019
DOI: 10.22159/ijap.2020v12i1.35683
|View full text |Cite
|
Sign up to set email alerts
|

Ziprasidone Hydrochloride Loaded Nanostructured Lipid Carriers (Nlcs) for Intranasal Delivery: Optimization and in Vivo Studies

Abstract: Objective: The present study was an attempt to systemically deliver the most desirable schizophrenia drug, ziprasidone hydrochloride (ZRS) via the intranasal route using nanostructured lipid carrier (NLC) approach. Methods:The desired ZRS loaded NLCs were developed using central composite statistical design and the developed formulation was monitored for improving ZRS bioavailability and their brain targeting efficacy.Results: Pharmacokinetic studies revealed a 10 fold increase (ZRS blood-brain ratio) for NLCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This study underscored the potential of lipid-based formulations as an effective strategy for precise central nervous system targeting, showcasing their versatility across diverse therapeutic applications. Adding to the body of evidence, Sivadasu et al [ 63 ] delved into the exploration of ziprasidone hydrochloride-loaded nanostructured lipid carriers for intranasal delivery. The formulation not only demonstrated promising results in terms of optimization but also exhibited notable outcomes in rigorous in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study underscored the potential of lipid-based formulations as an effective strategy for precise central nervous system targeting, showcasing their versatility across diverse therapeutic applications. Adding to the body of evidence, Sivadasu et al [ 63 ] delved into the exploration of ziprasidone hydrochloride-loaded nanostructured lipid carriers for intranasal delivery. The formulation not only demonstrated promising results in terms of optimization but also exhibited notable outcomes in rigorous in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ziprasidone-loaded NLCs were developed and tested by Sivadasu et al 185 for schizophrenia management. In vivo biodistribution studies revealed higher ziprasidone concen-trations in the brain at all time points following intranasal administration compared to the IV route with lower T max .…”
Section: Intranasal Drug Delivery Nanosystems For Targeted Drug Deliv...mentioning
confidence: 99%
“…Quality by design (QbD) is an essential concept for modern manufacturing processes of pharmaceutical products. [2][3][4][5] A scientific understanding of the manufacturing processes is crucial to realizing QbD. However, the mechanism underlying wet-granulation and tableting is unclear because of the complexity of the manufacturing processes, and consequently, it is difficult to identify critical process parameters (CPPs), critical material attributes (CMAs), as well as critical quality attributes (CQAs).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] These techniques provide systematic means to define CPPs, CMAs, and CQAs; however, a risk priority number (RPN) must be employed based on the expert knowledge. [4][5][6][7] Because the RPN is arbitrarily determined, we often encounter difficulties in objective scoring of RPN.…”
Section: Introductionmentioning
confidence: 99%